2007
DOI: 10.1093/rheumatology/ken041
|View full text |Cite
|
Sign up to set email alerts
|

A survey of rheumatology nurse specialists providing telephone helpline advice within England and Wales

Abstract: Objective. To characterize provision of telephone helpline services in rheumatology units in England and Wales. Methods. A questionnaire study of rheumatology nurse specialists (RNS) providing advice by a designated telephone helpline in England and Wales. Results. Responses were obtained from 164/185 rheumatology units (89%). Of the responding units, 154 (94%) employed RNS and 146 units provided telephone advice either by Allied Health Professionals or RNS. A total of 135 units confirmed that only RNS gave te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
0
10
0
3
Order By: Relevance
“…In several European countries, rheumatology nursing has developed into a recognised specialty with nurses undertaking both advanced and extended roles 1–3. Rheumatology nurses operate telephone advice lines, provide self-management support, patient education and counselling 4–8. Moreover, they participate in disease management, monitor disease-modifying treatments, give intra-articular injections, refer to other health professionals, prescribe drug treatments and help to manage comorbidities 2 9–12.…”
Section: Introductionmentioning
confidence: 99%
“…In several European countries, rheumatology nursing has developed into a recognised specialty with nurses undertaking both advanced and extended roles 1–3. Rheumatology nurses operate telephone advice lines, provide self-management support, patient education and counselling 4–8. Moreover, they participate in disease management, monitor disease-modifying treatments, give intra-articular injections, refer to other health professionals, prescribe drug treatments and help to manage comorbidities 2 9–12.…”
Section: Introductionmentioning
confidence: 99%
“…There is more data in adult chronic disease populations where a significant demand for telephone support has been shown [10-12]. Providing telephone support is becoming an integral part of adult rheumatology care in England and Wales [13]. It is valued by patients and enhances clinical service provision [14].…”
Section: Discussionmentioning
confidence: 99%
“…University of Limerick, Limerick, Ireland Background: Rheumatoid arthritis (RA) is a systemic inflammatory condition which results in pain, fatigue, joint stiffness and an increased risk of cardiovascular issues. Physical activity (PA) has been proven to help reduce the severity of these symptoms and the risk of cardiovascular disease [1]. However, recent literature has shown that people with rheumatoid arthritis do not meet PA guidelines [2].…”
Section: Completion Of Physical Activity Interventions For People Witmentioning
confidence: 99%
“…The patients were divided into two groups based on a prospective cohort (BETY group, n = 56; and control group, n = 35). BETY is a biopsychosocial exercise approach (1). It was performed in a period of one hour, 3 times a week for 12 weeks and included clinical pilates exercises, dance therapy-authentic movement and pain management information.…”
Section: Referencesmentioning
confidence: 99%